Evidence-based health information about pulmonary embolism: Assessing the quality, usability and readability of online and offline patient information - Anja Kalch; Aliscia Albani; Constanze Küchler; Helena Bilandzic; Simone Fischer; Inge Kirchberger (Elsevier, 2022)
Objective: Pulmonary embolism (PE) is the third most common cardiovascular disease worldwide. However, public awareness is considerably lower than for myocardial infarction or stroke. Patients suffering from PE complain about the lack of (understandable) information and express high informational needs. To uncover if reliable information is indeed scarce, this study evaluates the quantity and quality of existing patient information for tertiary prevention using an evidence-based health information paradigm. Methods: We conducted a quantitative content analysis (n = 21 patient information brochures; n = 67 websites) evaluating content categories addressed, methodical quality, usability, and readability. Results: Results show that there is not enough patient information material focusing on PE as a main topic. Existing patient information material is mostly incomplete, difficult to understand, and low in actionability as well as readability. Conclusion: Our systematic analysis reveals the need for more high-quality patient information on PE as part of effective tertiary prevention. Innovation: This is the first review analyzing content, methodical quality, readability, and usability of patient information on PE. The findings of this analysis are guiding the development of an innovative, evidence-based patient information on PE aiming to support patients' informational needs and their self-care behavior.